Realization of Photo‐Thermal Metathesis Under Microwave Irradiation Conditions: An Entry to Triquinane Frameworks. Issue 11 (1st October 2019) - Kotha, Sambasivarao; Cheekatla, Subba Rao; Meshram, Milind; Bandi, Vijayalakshmi; Seema, Vittal
Abstract: We report a simple and convenient synthetic route to cis, syn, cis triquinane frameworks under microwave irradiation conditions starting with cage diones. This is feasible because of the substituents present in the precursors, which facilitate the metathesis under milder reaction conditions as compared to normal flash vacuum pyrolysis conditions (∼600 °C). Isomerization of the double bond was realized under microwave irradiation to deliver the other triquinanes, which are useful precursors for natural product synthesis. Abstract : Microwave irradiation conditions to assemble a variety of cis, syn, cis ‐triquinane frameworks from cage diones as an alternative to flash vacuum pyrolysis conditions have been reported.